Synthesis and Self‐assembly of a Helical Polymer Grafted from a Foldable Polyurethane Scaffold. Issue 24 (14th October 2019) - Barman, Ranajit; Dey, Pradip; Mondal, Tathagata; Ghosh, Suhrit
Abstract: Herein a polyurethane graft poly‐l ‐glutamate amphiphilic copolymer was synthesized from a polyurethane (PU)‐based macro‐initiator (containing pendant primary amine groups) through the ring opening polymerization of N ‐carboxy anhydride of γ‐benzyl‐l ‐glutamate (BLG‐NCA ). On average, twenty two l ‐glutamic acids were grafted from each amino group which was pendant on the polyurethane chain with 10 repeating units. The grafted polymer (PU‐PP‐1 ) exhibits self‐assembly to produce a hydrogel in a wide pH window ranging from pH 5.0 to 8.0 with a critical gelation concentration (CGC) of 5.0 wt % (w/v) at pH 7.4. Furthermore, circular dichroism study revealed the transition of the α‐helix to a random coil upon increasing the pH. Due to the protonation of side chains at pH 4.0, PU‐PP‐1 adopted an α‐helical conformation whereas at pH >8.0 the side‐chain carboxylic acid groups of the PLGAs were ionized, leading to the formation of an extended random coil conformation as a result of charge repulsion. Conformational switching was also supported by FTIR spectroscopy. Abstract : Self‐assembly of graft polypeptide : This article demonstrates the synthesis of a new class of brush polymer consisting of a pH‐responsive poly(l ‐glutamic acid) grafted on a hydrophobic foldable polyurethane backbone in which both the backbone and the pendant chains adopt a well‐defined secondary structure in solution, resulting in pH‐dependent hierarchical assembly and gelation in water.